An Experimental and Analytical Study on the Bending Performance of CFRP-Reinforced Glulam Beams - He, Minjuan; Wang, Yuxuan; Li, Zheng; Zhou, Lina; Tong, Yichang; Sun, Xiaofeng (Frontiers in Materials, 2022)
The fiber reinforced polymer is one kind of composite material made of synthetic fiber and resin, which has attracted the research interests for the reinforcement of timber elements. In this study, a total of 18 glued-laminated (glulam) beams unreinforced or reinforced with internally embedded carbon fiber reinforced polymer (CFRP) sheets were tested under four-point bending loads. Clear specimens of Douglas fir were also tested to obtain the material properties of glulam. For the CFRP reinforced glulam beams, the influences of the strengthening ratio, the modulus of elasticity of the CFRP, and the CFRP arrangement on their bending performance were experimentally investigated, respectively. Subsequently, a finite element model of glulam beams was developed and verified with the experimental results; furthermore, a general theoretical model considering the typical tensile failure mode of the reinforced glulam beams was employed to predict the bending-resisting capacities of the CFRP reinforced glulam beams, based on the plane-section assumption that was verified by the bending tests in this project. It is found that the CFRP reinforced glulam beams are featured with relatively ductile bending failure, compared to the brittle tensile failure of the unreinforced ones. Besides, compared to the unreinforced glulam beams, the compressive properties of the uppermost grain of the glulam can be more fully utilized in the CFRP reinforced ones. By using one CFRP sheet with a strengthening ratio of 0.040 % for reinforcing the glulam beams, the bending-resisting capacity and the maximum deflection can be enhanced approximately by 6.51 % and by 12.02 %, respectively. The difference between the experimental results and the numerical results as well as that between the experimental results and analytical results are within 20 % and 10 %, respectively.